(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Hotel service means renting of rooms, houses, or other lodging accommodations for a fee, including all services offered at the hotel, including, but not limited to, business centre services, massage service, swimming pool fees, laundry services, etc., whether paid by a guest of the hotel or a visitor to the hotel.